ijps 2021
DOI: 10.36468/pharmaceutical-sciences.869
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition, Antioxidant and Antityrosinase Activities, and Quantification of (+)-Dihydrokaempferol of Different Parts of Manilkara zapota

Abstract: Chunhakant et al.: Quantification of (+)-Dihydrokaempferol in Manilkara zapotaFree radicals can cause oxidative damage in biomolecules and lead to pathological diseases. Antioxidants can protect against the oxidation of living cells. The aim of this study was to evaluate the total phenolic and flavonoid contents and the antioxidant and antityrosinase activities of different parts of Manilkara zapota and measure the quantity of (+)-dihydrokaempferol in different plant parts. The bark, flowers, fruit, leaves, ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In this study, the MeOH extract of M. hexandra bark showed an IC 50 of 88.7 μ g/mL. Furthermore, a recent study, conducted by Chunhakant and Chaicharoenpong [ 24 ] showed that the IC 50 of the MeOH and the aqueous bark extract of M. zapota were 66.4 and 78.0 μ g/mL, respectively. Therefore, its antioxidant potency was less important than that of the bark MeOH extract of M. mabokeensis Aubrév (IC 50 : 18.7 μ g/mL).…”
Section: Resultssupporting
confidence: 57%
“…In this study, the MeOH extract of M. hexandra bark showed an IC 50 of 88.7 μ g/mL. Furthermore, a recent study, conducted by Chunhakant and Chaicharoenpong [ 24 ] showed that the IC 50 of the MeOH and the aqueous bark extract of M. zapota were 66.4 and 78.0 μ g/mL, respectively. Therefore, its antioxidant potency was less important than that of the bark MeOH extract of M. mabokeensis Aubrév (IC 50 : 18.7 μ g/mL).…”
Section: Resultssupporting
confidence: 57%
“…Results demonstrated strong reducing potential with 53.3 ± 2.85 and 40.09 ± 3.61 μM AEAC, respectively, which suggests a significant electron-donating capacity. Ethanolic bark extract also showed antioxidant capacity in DPPH assay with IC 50 = 16.83 μg/ml, compared process can affect antioxidant potential (28). Flavonoids are polyphenols that have significant antioxidant activity through direct scavenging of free radicals, followed by the inactivation and inhibition of lipid peroxidation by metal ion chelation (61).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In both extracts, (+)-dihydrokaempferol was detected, and the highest (+)-dihydrokaempferol concentration was found in the methanolic bark extract. This suggests a correlation between anti-tyrosinase activity and this specific compound (28). To determine its antioxidant activity, Kashif and Akhtar (94) developed a natural emulgel sunscreen loaded with chicozapote fruit extract.…”
Section: Anti-aging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds are the most common group in plants (GutiErrez-Grijalva et al, 2016). A previous study found that sapodilla leaves had the highest total phenolic content, followed by the flowers (Chunhakant & Chaicharoenpong, 2021). Sapodilla leaves were freeze-dried to determine the effect of leaf maturity on phytochemical content.…”
Section: Total Phytochemicalsmentioning
confidence: 99%